All-Optical Arbitrary-Point Stable Quadruple Frequency Dissemination With Photonic Microwave Phase Conjugation - Haojie Wang; Xiaoxiao Xue; Shangyuan Li; Xiaoping Zheng (IEEE Photonics Journal, 2018)
We present an all-optical stable quadruple frequency dissemination for an arbitrary-access-point fiber-optic loop link using photonic microwave phase conjugation. A two-tone optical carrier is transferred as a round-trip probe signal to undergo the propagation delay of the entire fiber loop link. When the probe signal returns to the local site, a Mach–Zehnder modulator biased at the null point is used as a phase conjugator to reverse its phase, thus, implementing photonic microwave phase conjugation. At an arbitrary remote site, the phase-conjugated signal is photomixed with a tapped forward transferred signal to obtain a stable frequency-quadrupled radio frequency (RF) signal in which the fiber-induced phase drift is automatically eliminated. Owing to photonic microwave phase conjugation and photomixing, the local oscillator leakage and harmonics interference of electrical mixers employed in the previous compensation schemes can be avoided. We demonstrate the stable dissemination of a 20-GHz frequency-quadrupled RF signal to two arbitrary remote sites located at a 20-km fiber-optic loop link. The residual root-mean-square timing jitter in an hour is no more than 0.86 ps. The relative frequency stability of 10 −16 level at 1000 s averaging time can be realized at every remote site.